VHDL coding and logic synthesis with Synopsys - Lee, Weng Fook. (Academic Press, 2000)
This book provides the most up-to-date coverage using the Synopsys program in the design of integrated circuits. The incorporation of "synthesis tools" is the most popular new method of designing integrated circuits for higher speeds covering smaller surface areas. Synopsys is the dominant computer-aided circuit design program in the world. All of the major circuit manufacturers and ASIC design firms use Synopsys. In addition, Synopsys is used in teaching and laboratories at over 600 universities. * First practical guide to using synthesis with Synopsys * Synopsys is the #1 design program for IC design.